PENGARUH HANDOUT BERORIENTASI PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR IPA-FISIKA SISWA KELAS IX SMP PERTIWI 2 PADANG - Giffi Febri Yeni; Amali Putra; Hufri Hufri (Universitas Negeri Padang, 2015)
This study aims to investigate the influence of Handout oriented scientific approach to science learning outcomes-physics class IX students of SMP Earth 2 Padang in the 1st half of the school year 2014/2015. The research is a